2020
DOI: 10.1021/acs.jpcb.9b11137
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanism of Acetamide in Deep Eutectic Solvents

Abstract: Over the last couple of decades, deep eutectic solvents (DESs) have emerged as novel alternatives to ionic liquids that are extensively used in synthesis of innovative materials, metal processing, catalysis, etc. However, their usage is limited, primarily because of the large viscosity and poor conductivity. Therefore, an understanding of the molecular origin of these properties is essential to improve their industrial applicability. Here, we present the report of the nanoscopic diffusion mechanism of acetamid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 58 publications
2
50
0
Order By: Relevance
“…120 Alternative Li salts such as lithium triflate (LiTfO), lithium perchlorate (LiClO4) and lithium bromide (LiBr) have been used as well. 11,130,[133][134][135][136][137] It has been shown that mixtures of Li salts (LiClO4, LiBr, and lithium nitrate LiNO3) and AA in a molar ratio of approximately 1:4 form DESs having freezing points below room temperature. 11 Apparently the depression of freezing points in these systems can be ascribed to the ability of these salts to break the interamide hydrogen bonding.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%
See 2 more Smart Citations
“…120 Alternative Li salts such as lithium triflate (LiTfO), lithium perchlorate (LiClO4) and lithium bromide (LiBr) have been used as well. 11,130,[133][134][135][136][137] It has been shown that mixtures of Li salts (LiClO4, LiBr, and lithium nitrate LiNO3) and AA in a molar ratio of approximately 1:4 form DESs having freezing points below room temperature. 11 Apparently the depression of freezing points in these systems can be ascribed to the ability of these salts to break the interamide hydrogen bonding.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%
“…140 The nanoscale dynamics of some of these AA-based DESs (with LiNO3 or LiClO4) has been investigated by Srinivasan and coworkers using quasielastic neutron scattering (QENS) and MD simulations. [134][135][136] Results indicate that the AA molecules form a hydrogen-bond network with its neighbouring set of molecules resulting in a transient cage and the molecular diffusion of AA involves a combination of localized diffusion and cage-to-cage jump diffusion. 134,135 The localized diffusion process is associated with the dynamics of the molecules while it is trapped by an H-bond with neighbouring AA molecules and ions, whereas the jump diffusion process is associated with the diffusion of the molecule between two transient cage.…”
Section: Lithium Salts and Amidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetamide (also known as ethanamide or acetic acid amide) belongs to the class of organic compounds known as carboxamides acids with the formula CH 3 CONH 2 Fig. 2 [59].…”
Section: An Overview Of Acetamide Derivatives As Possible Therapeutic Candidatesmentioning
confidence: 99%
“…Further, a novel series of fluoro-substituted chalcone derivatives (62a-i) were prepared by three steps reaction. First phloroglucinol (58) was treated with acetic anhydride in the presence of methane sulfonic acid at 80 °C to achieve compound 1,1′,1′'-(2,4,6-trihydroxybenzene-1,3,5-triyl) triethanone (59). The next step was to obtain compound 1,1′,1′'-(2,4,6-Trimethoxybenzene-1,3,5-triyl)triethanone (60) by the reaction of compound (59) with dimethyl sulphate.…”
Section: Introduction To Synthesis Of Chalcone and Its Derivativesmentioning
confidence: 99%